Basics of inclusive education for children with special needs in Nigeria (2012)
Inclusive education policy emerged in response to the declaration on Education For All by the United Nations Educational Scientific and Cultural Organization (UNESCO) several years ago. Actually, inclusive education represents the latest attempt in the provision of placement options or alternative programmes worldwide for children with special needs. It ensures that children with special needs are educated within the regular education System, free of all forms of labelling, stigmatization and segregation. This paper discussed the basic elements existing in thriving inclusive educational settings. It also discussed the benefits of inclusive education to children with special needs, as well as the current state of inclusive education in Nigeria. It recommended that a nationwide awareness programme highlighting the benefits of inclusive education should be carried out to ensure adequate training, planning, implementation and support towards achieving Education for All in Nigeria.